The impact of lockdowns or severe social restrictions during COVID-19 pandemic on glycaemic control of adults suffering with type 2 diabetes mellitus: a review - Sheik, Sanaulla; Sultana, Samar; Haqh, Shafia (International Journal Of Community Medicine And Public Health, 2023)
Glycemic control in diabetes has shown to improve insulin sensitivity and reduce both microvascular and microvascular complications in diabetes mellitus. In 2020, with the globe facing COVID-19 pandemic the governments and authorities resorted to lockdowns to reduce the spread of infection. We aimed to find the impact of lockdowns during COVID-19 pandemic on glycaemic control of adults suffering with type 2 diabetes mellitus. (T2DM). We systematically searched 5 medical databases MEDLINE via PubMed, Embase, CINAHL, web of science and Cochrane library up to 16th November 2021 using key terms. Total of 24899 articles were identified by the search, of which 17571 articles were excluded for duplication, 7303 were excluded after screening for title and abstract, and further 16 articles excluded after full text review. We analyzed the final 9 observational studies fulfilling the criteria. There are 2177 participants from final 9 observational studies, 5 studies showed worsening glycemic control during lockdown period, 2 reported improvement and 2 showed no significant change. We noticed that weight was correlating with glycated hemoglobin change. Studies with lockdown period >10weeks reported greater HbA1c deterioration and farther HbA1c when done from start of lockdown, the higher HbA1c values noticed. Glycemic control overall in type 2 diabetes has worsened due to lockdown measures which may be due to reduced physical activity, change in diet or psychosocial changes. There has also been increase in BMI (Body Mass Index) correlating with raise in HbA1c. More in-depth review is required into long term impact of lockdowns on diabetes.